'Frozen shoulder' is ill-defined. How can it be described better?. Issue 5 (1st May 2020) - Abrassart, Sophie; Kolo, Franck; Piotton, Sébastian; Chih-Hao Chiu, Joe; Stirling, Patrick; Hoffmeyer, Pierre; Lädermann, Alexandre
Abstract : Frozen shoulder, a common and debilitating shoulder complaint, has been the subject of uncertainty within the scientific literature and clinical practice. We performed an electronic PubMed search on all (1559) articles mentioning 'frozen shoulder' or 'adhesive capsulitis' to understand and qualify the range of naming, classification and natural history of the disease. We identified and reviewed six key thought leadership papers published in the past 10 years and all (24) systematic reviews published on frozen shoulder or adhesive capsulitis in the past five years. This revealed that, while key thought leaders such as the ISAKOS Upper Extremity Council are unequivocal that 'adhesive capsulitis' is an inappropriate term, the long-term and short-term trends showed the literature (63% of systematic reviews assessed) preferred 'adhesive capsulitis'. The literature was divided as to whether or not to classify the complaint as primary only (9 of 24) or primary and secondary (9 of 24); six did not touch on classification. Furthermore, despite a systematic review in 2016 showing no evidence to support a three-phase self-limiting progression of frozen shoulder, 11 of 12 (92%) systematic reviews that mentioned phasing described a three-phase progression. Eight (33%) described it as 'self-limiting', three (13%) described it as self-limiting in 'nearly all' or 'most' cases, and six (25%) stated that it was not self-limiting; seven (29%) did not touch on disease resolution. We call for a data and patient-oriented approach to the classification and description of the natural history of the disease, and recommend authors and clinicians (1) use the term 'frozen shoulder' over 'adhesive capsulitis', (2) use an updated definition of the disease which recognizes the often severe pain suffered, and (3) avoid the confusing and potentially harmful repetition of the natural history of the disease as a three-phase, self-limiting condition. Cite this article: EFORT Open Rev 2020;5:273-279.DOI: 10.1302/2058-5241.5.190032